Unemployment and Labor Market Rigidities: Europe versus North America. - Nickell, S (1997)
The received wisdom tells us that the rigidity and inflexibility of European job markets relative to that in the United States is the reason why Europe has high unemployment. This paper argues that this broad brush analysis is simply too vague to be useful. Indeed it is probably positively misleading. Many labor market institutions that conventionally come under the heading of rigidities have no observable impact on unemployment and may otherwise serve a useful purpose.